THE OGHUZ EPIC STORIES IN THE SELJUK ERA - Аникеева Татьяна A. (History, Archeology and Ethnography of the Caucasus, 2019)
The article is devoted to several monuments of the Turkish folklore and literature the formation of which dates back to the time of Seljukids in Asia Minor: “The Book of Dede Korkut”, “The Story of Seyyid Battal” (“Battal-nameh”, or “Seyyid Battal gazavatnamesi”) and “The Tale of Melik Danishmend” (“Danishmend-nameh”). “Kitab-i dedem Korkut”, The Book of Dede Korkut”…is the only medieval epic of the Turkic peoples which has remained in written form until today. “The Book of “The Book of Dede Korkut” according to the Dresden manuscript consists of twelve songs-legends (and according to the Vatican manuscript – of six tales which have been called oguznameh), which tell of the Oghuz heroes’ deeds. The main plot which core is framed by these stories, is the struggle of the Oghuz tribes against the infidels, non-Muslims in the lands of Asia Minor and Transcaucasia, as well as strife among the Oghuz themselves. This text reflects both the events of early Turkic semi-legendary history (not only historical facts, but also a set of mythological beliefs) and later events connected with the spread of their power in Asia Minor and with their contacts with Byzantium. The stories that comprise ““The Book of Dede Korkut” display a clear connection with both the common Turkic literary and folk tradition and more recent strata. Battal-nаmeh and Danishmend-nameh both are monuments of a written epos within the boundaries of oral recently some legends related to the Oghuz epic (both “The story of Battal” and some tales from “The Book of Dede Korkut”) have continued to exist in oral and literal form on the territories of modern Turkey and Transcaucasia.